Numerical Investigation on the Influence of In-Plane Damage on the Out-of-Plane Behavior of Masonry Infill Walls - Xiaomin Wang; Weitong Zhao; Jingchang Kong; Tiejun Zhao (Advances in Civil Engineering)
This study presents a finite element model to investigate the bidirectional seismic behavior of masonry infill walls. The test data are utilized to verify the numerical model. The comparison between the analytical and the experimental results indicates that the finite element model can successfully predict the failure mode, stiffness, and strength of the masonry infill wall. Based on the model, the effects of aspect ratio (height to length), slenderness ratio (height to thickness), and masonry strength on the out-of-plane (OOP) response of infill wall with in-plane (IP) damage are explored. Considering the aspect ratio, slenderness ratio, and masonry strength of infill wall, the OOP behavior of infill wall with and without IP damage is studied. Finally the reduction of the stiffness and strength in the OOP direction, due to the IP damage, is discussed.